(untitled) (Educação e Pesquisa, 2023)
Higher education institutions have undergone relevant changes during the last decades. These changes force universities to behave as market organizations aiming to collect resources from tuition in a competitive environment, hindering their public role. Since student tuition is the main financial entrance for Chilean universities, they have been compelled to transform themselves at the management level to be competitive, attract students and reach funds from enrollment. This article aims to examine how the governance and management of a Chilean state university face the pressures to position itself competitively in the recruitment of undergraduate students and what tensions this generates internally within the central administration. The hypothesis guiding this study is that these pressures generate a series of organizational and cultural tensions in the central administration. We studied a Chilean upper-sized, research-oriented, state university through semi-structured interviews with managers at the core level. We analyzed the strategies developed in the educational market and the rising struggles that emerged from the transformation, looking at the institutional identity. Results show that the university changes its structure due to the market pressures at the organizational level. These changes take shape by designing strategic plans and including new professional staff to improve their position in the educational market. Also, the university adapts these innovations as part of its institutional ethos within the new public management framework. The article ends with a summary and suggestions for future studies of organizational change in universities.